Isolasi, Karakterisasi dan Amobilisasi Î±-Amilase dari Aspergillus niger FNCC 6018 - Nisa', Khairun (Chem Info Journal, 2013)
Aspergillus niger FNCC 6018. The purposes of this research are to get specific activity data of isolated Î±-amylase from Aspergillus niger FNCC 6018, get optimum condition of enzyme data, include: pH and temperature, and get activity data of immobilized Î±-amylase in matrix bacto agar and recurrence test. The method is use in this research to determine Î±-amylase activity test by measuring maltose that produce from Î±-amylase which hydrolize amylose with Bernfeld method using DNS (3,5-dinitrosalicylic acid). Amount of protein was measured by Lowry method using standard BSA (Bovine Serum Albumin). The result of this research show that Î±-amylase enzyme isolated from Aspergillus niger FNCC 6018 which ammonium sulphate fraction 3 (40-60%) has the highest specific activity amount 5.7 Unit/mg protein. Optimum condition Î±-amylase from Aspergillus niger FNCC 6018 was achieved at optimum pH value 5.0 and temperature 36Î¿C. Immobilized Î±-amylase in matrix bacto agar had specific activity amount 1.95 Unit/mg protein and use until twice recurrence.